Students' Perceptions towards E-Learning Platform in EFL Classroom - Daipah Daipah; Hanif Nurcholish Adiantika; Fitri Aprianti (National Conference on Language, Education, and Technology Proceeding, 2021)
This study aims to analyze students about learning using the e-learning platform and measure students' perceptions about learning using the e-learning platform. At one of the private University in Cirebon. This research uses qualitative research with case study design. The data source of this research is a data source in the form of primary or main data sources where data collection is obtained through questionnaire and interview. To analyze the data is done through three stages, namely data reduction, data presentation and verification or conclusion. Then the triangulation of data and sources is used as a means of checking the validity of a data. The results of the study illustrate that first, the positive perception that students have of learning through the E-Learning platform during the Covid-19 pandemic, that learning using the E-Learning platform is effective, the ELearning platform can assist students in carrying out online learning during the Covid-19 pandemic. Second, the E-Learning platform in online learning during the Covid-19 pandemic is very useful for continuing to learn where students want to learn the media provided by lecturers such as the e-Learning platform, the use of the E-Learning platform is useful for online learning for now learning is done online. by using the E-Learning platform so that students can continue to learn.